Crowdsourced data reveal threats to household food security in near real-time during COVID-19 pandemic - Adewopo, Julius; Hermosilla, Gloria Solano; Micale, Fabio; Colen, Liesbeth (International Food Policy Research Institute, 2022)
The COVID-19 pandemic and related lockdown measures have disrupted food systems globally, leading to fluctuations in the prices of some food commodities, from local to national levels. Yet detailed data-driven evidence of the extent, timing, and localization of the impact on food security are rarely available quickly enough or with sufficient granularity to guide policy responses.